Coordination between deformation, precipitation, and erosion during orogenic growth - Xiaoping Yuan; Yuqiang Li; Sascha Brune; Kai Li; Michaël Pons; Sebastian G. Wolf (Nature Communications)
Abstract Crustal thickening associated with orogenic growth elevates topography, causing orographic enhancement of precipitation, which in turn facilitates local erosion and possibly intensifies localization of deformation. How these three processes—deformation, precipitation, and erosion—coordinate during orogenic growth remains unknown. Here, we present a numerical model where tectonics, surface processes, and orographic precipitation are tightly coupled, and explore the impact on low, intermediate, and high erodibility orogens. We show that, for intermediate erodibility models, rock uplift rates and precipitation rates correlate well with erosion rates during the formation of orogenic plateaus with high correlation coefficients of ~0.9 between rock uplift and erosion rates, and ~0.8 between precipitation and erosion rates. We demonstrate a cyclicity of correlation evolution among uplift, precipitation, and erosion rates through the development of new faults propagating outward. These results shed insights into the relative tectonic or climatic control on erosion in active orogens (e.g., Himalayas, Central Andes, and Southern Alps of New Zealand), and provide a plausible explanation for several conflicting data and interpretations in the Himalayas, which depend on the stage of maturity of the newest fault and the relative locations to old faults.